Family incertae cedis * - Bird, Graham J. (Zootaxa, 2007)
A heterogeneous collection of tanaidomorphan species that are no longer assigned to existing families is recorded in the Kurile-Kamchatka Trench and the Japan Trench, belonging to six genera: Akanthophoreus, Chauliopleona, Exspina, Leptognathia sensu lato, Leptognathioides and Robustochelia. Three new species of Akanthophoreus Sieg, 1986 are described, and four putative taxa are outlined to facilitate consistent identification in future studies.